A pragmatic assessment of the placement of oxygen when given for exercise induced dyspnoea. Issue 7 (1st July 2000) - Killen, J W W; Corris, P A
Abstract : BACKGROUND: It is uncertain whether patients with chronic obstructive pulmonary disease (COPD) given oxygen for symptom relief should be advised to use it before or after exertion. METHODS: Eighteen patients with smoking related COPD who desaturated on exercise were given oxygen or air from a cylinder in a single blind manner and in an order determined by Latin square randomisation, before and after ascending stairs. The time of ascent, desaturation, and dyspnoea associated with the ascent was compared across the treatment groups. RESULTS: Oxygen given before or after the ascent reduced maximal dyspnoea from 49.1 mm (95% CI 35.5 to 62.7) to 41.7 mm (95% CI 34.3 to 49.1) of a 100 mm visual analogue scale, reduced desaturation (oxygen before 4.9% (95% CI 3.6 to 6.2), oxygen after 6.4% (5.3 to 7.5), air before and after 8.2% (6.7 to 9.7%)), but did not affect time of ascent (air before: 5.1 s (95% CI 3.4 to 6.9) reduction from training ascent; oxygen before: 6.1 s (95% CI 2.9 to 9.2) reduction). CONCLUSIONS: Oxygen prescribed for symptomatic relief of dyspnoea benefits selected patients with COPD, but it seems not to matter whether it is taken before or after exertion.